Investigation into boiler corrosion on the historic vessel SL Dolly. - Turnbull, I. A.; Robinson, M. J. (Maney, 2005)
When SL Dolly was recovered from Ullswater after being submerged for 67 years, the wrought iron boiler was found to have surprisingly little corrosion. This article describes the results of a project to investigate the reasons for this behaviour and determine whether it was a property of the wrought iron or a consequence of the lakebed environment. Weight loss measurements and electrochemical impedance spectroscopy were used to compare the corrosion rates of wrought iron and modern boiler steel exposed to tap water and samples of lake water and lakebed sediment. A corrosion probe was used to make in situ linear polarisation resistance measurements at the spot where Dolly sank. The corrosion rate of wrought iron on the lakebed was estimated to be in the range 0Ã Â·018Ã¢Â Â 0Ã Â·030 mm year-1, which corresponds to a metal loss of 1Ã Â·2Ã¢Â Â 2Ã Â·0 mm over the 67 year period; this metal loss is consistent with the condition of the boiler. The effects of microstructure, material composition and water chemistry are considered in detail, and it is concluded that the low oxygen content and the low concentration of dissolved solids in the lake water were the underlying causes of the observed corrosion be
Keywords: Boiler corrosion